Employee Perceptions of Organisational Emotional Intelligence and Psychological Capital Amongst Public Servants in Uganda - Kabagabe, Jolly Byarugaba; Kriek, Drikus (Journal of Organizational Psychology, 2021)
We developed and tested a model examining the association between organisational emotional intelligence and psychological capital in the workplace. Employing the organisational positivity argument, we proposed that organisational emotional intelligence be associated with higher order psychological capital. We tested our hypothesis using cross sectional data from employees from public organisations in Uganda. The study established that employee perceptions emotional intelligence organization organisations could be associated with employee psychological capital. organisational managers should develop organisational emotional intelligence which is manifested through job happiness, compensation satisfaction, supervisory leadership, organisational cohesiveness, responsiveness, work life stress management, diversity and anger management, and positive impression management creating a positive emotionally intelligent organisatiion to develop psychological capital for positive outcomes.